Impact of donor age on long‐term outcomes after delayed graft function: 10‐year follow‐up. (1st December 2012) - Lapointe, Isabelle; Lachance, Jean‐Guy; Noël, Réal; Côté, Isabelle; Caumartin, Yves; Agharazii, Mohsen; Houde, Isabelle; Rousseau‐Gagnon, Mathieu; Joseph Kim, S.; De, Sacha A.
Summary Delayed graft function (DGF) has a negative impact on graft survival in donation after brain death (DBD) but not for donation after cardiac death (DCD) kidneys. However, older donor age is associated with graft loss in DCD transplants. We sought to examine the interaction between donor age and DGF in DBD kidneys. This is a single‐center, retrospective review of 657 consecutive DBD recipients transplanted between 1990 and 2005. We stratified the cohort by decades of donor age and studied the association between DGF and graft failure using Cox models. The risk of graft loss associated with DGF was not significantly increased for donor age below 60 years (adjusted hazard ratio [aHR] 1.12, 1.51, and 0.90, respectively, for age <40, 41–50 and 51–60 years) but significantly increased after 60 years (aHR 2.67; P = 0.019). Analysis of death‐censored graft failure yielded similar results for donor age below 60 years and showed a substantially increased risk with donors above 60 years (aHR 6.98, P = 0.002). This analysis reveals an unexpectedly high impact of older donor age on the association between DGF and renal transplant outcomes. Further research is needed to determine the best use of kidneys from donors above 60 years old, where DGF is expected.